New definitions of pre-extensively and extensively drug-resistant tuberculosis: update from the World Health Organization. Issue 4 (8th April 2021) - Viney, Kerri; Linh, Nguyen Nhat; Gegia, Medea; Zignol, Matteo; Glaziou, Philippe; Ismail, Nazir; Kasaeva, Tereza; Mirzayev, Fuad
Multidrug-resistant tuberculosis (MDR-TB), defined as Mycobacterium tuberculosis with resistance to at least isoniazid and rifampicin [1], emerged as a threat to tuberculosis (TB) control worldwide in the 1990s [2]. This form of TB required the use of second-line drugs that were less effective, more toxic and costlier than first-line isoniazid- and rifampicin-based regimens. MDR-TB was one of the first infectious conditions to alert national authorities worldwide to the importance of antimicrobial resistance as a public health challenge of the future, further emphasised by outbreaks of MDR-TB in the USA and Europe [3–5]. Recognising the global importance of this emerging problem, the World Health Organization (WHO) released its first guidelines on the management of drug-resistant TB in 1996 and has updated them regularly since [1, 6]. The definition of extensively drug resistant tuberculosis has been updated by the World Health Organization and pre-extensively drug-resistant tuberculosis has been defined https://bit.ly/30Fdffc